Biodiversity, Phylogeny, and Evolutionary Dynamics of Gall Midges on Japanese Beech Trees - Shinnosuke Mori; Yugo Dhakhwa; Makoto Tokuda; Yoko Saikawa (Ecology and Evolution)
ABSTRACT The Japanese Archipelago harbors unique beech flora (Fagus L.; Fagaceae), with a parapatric distribution of two endemic species, F. crenata and F. japonica, upon which a diverse array of 34 types of leaf galls induced by gall midges (Diptera: Cecidomyiidae) has been documented. The inducers of most of these galls remain undescribed, and their phylogenetic relationships with known taxa are still poorly understood. In this study, we collected 29 types of leaf galls from the two Japanese Fagus species, including 6 previously unreported types, and sequenced the cytochrome c oxidase subunit I mitochondrial gene of the inducers to infer maximum‐likelihood and Bayesian time‐calibrated phylogenies. Our phylogenetic analyses revealed that the Fagus‐feeding guild forms a monophyletic clade within the tribe Dasineurini, with F. crenata‐feeding taxa occupying a basal position within the lineage. These taxa are closely related to the genera Hartigiola and Mikiola and have likely undergone adaptive radiation on the leaves of F. crenata and F. japonica in the ecologically segregated Japanese Archipelago since the Miocene period, accompanied by multiple host shifts between the two Fagus species and location shifts within their leaves.